A Research Overview of the Methodologies Used in Codification of Famous Gharib ul Hadith’s Books - Shah, Muhammad; Jan, Muhammad Naeem (Journal of Islamic and Religious Studies, 2017)
Methodical codification of “Gharib ul Hadith” books started during second century. Abu Ubaida Mua‘mmar bin Muthanna, an Iraqi scholar, pioneered the field. Afterwards numerous scholars have written books on “Gharib ul Hadith” but they followed different methodologies for their compositions. Some of them have written Hadith's disorderly, and then explained all Gharib words appearing in the Hadith. This method appears in most part of their writings. Some of the scholars have observed jurisprudential method for their creations. Others followed methodology of explaining Gharib words by organizing Hadith's; first from Prophet Muhammad, then from sahabas (companions of Prophet Muhammad s.a.w), and finally from Taba’een (immediate followers). However, some sorted Hadith in alphabetical order. This research article presented a detailed analytical review of different methodologies adopted in famous “Gharib ul Hadith” Books.